Management of a rare case of peripheral squamous odontogenic tumor of the gingiva - Ramamurti Anjana; Nirupama Murali; Narasimhan Malathi; Ranga Rao Suresh (Wolters Kluwer Medknow Publications, 2016)
Odontogenic tumors (OTs) arising from the periodontium are quite rare. Squamous OT (SOT) is one such neoplasm which has an exceedingly rare occurrence. According to the literature, there have been very few reported cases of SOT with a very small percentage involving the gingiva. Most of the times, these tumors are located within the bone, only a very few peripheral cases been noted so far. Although predominantly benign, the possibility of a malignant transformation prevails. Our case describes a rare presentation of a peripheral SOT involving the upper anterior gingiva in a 59-year-old patient, which presented clinically as a firm and fibrotic swelling. An excisional biopsy was performed as a part of surgical management and for microscopic evaluation to confirm the clinical diagnosis. A soft tissue graft was harvested from an edentulous area to cover the deficit at the surgical site. The patient was evaluated at periodic intervals to assess the healing outcome and for any recurrence of the lesion.